1996
DOI: 10.1116/1.589143
|View full text |Cite
|
Sign up to set email alerts
|

Scanning force microscopy for the study of domain structure in ferroelectric thin films

Abstract: A piezoresponse technique based on scanning force microscopy (SFM) has been used for studying domain structure in ferroelectric thin films. Studies were performed on Pb(Zrx,Ti1−x)O3(PZT) thin films produced by a sol–gel method. The piezoresponse images of the PZT films were taken before and after inducing polarization in the films by applying a direct current voltage between the bottom electrode and the SFM tip. Polarization induced patterns were written with 20 V pulses and subsequently imaged by the SFM piez… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(116 citation statements)
references
References 14 publications
2
113
0
1
Order By: Relevance
“…This method, described in detail in previous publications, [4][5][6] is similar to strain observation by other scanning probe techniques. [7][8][9] Using the lock-in technique, the domain structure can be visualized by monitoring the first harmonic signal ͑piezoresponse͒ caused by the piezoelectric effect, since the phase of this signal depends on the sign of the piezoelectric coefficient and on the polarization direction.…”
Section: H Tokumotomentioning
confidence: 88%
See 1 more Smart Citation
“…This method, described in detail in previous publications, [4][5][6] is similar to strain observation by other scanning probe techniques. [7][8][9] Using the lock-in technique, the domain structure can be visualized by monitoring the first harmonic signal ͑piezoresponse͒ caused by the piezoelectric effect, since the phase of this signal depends on the sign of the piezoelectric coefficient and on the polarization direction.…”
Section: H Tokumotomentioning
confidence: 88%
“…Recently, it has been demonstrated that scanning force microscopy ͑SFM͒ is a useful technique for investigation of ferroelectric materials, providing high-resolution visualization of ferroelectric domains. [2][3][4][5][6] In the present letter we use SFM to perform a study of domain structures and switching behavior of PZT ferroelectric thin films integrated into heterostructures with different electrodes, which yield different fatigue characteristics.…”
Section: H Tokumotomentioning
confidence: 99%
“…11,12 Further progress in these fields necessitates fundamental studies of ferroelectric domain structures and dynamics and polarization-switching phenomena on the nanoscale. In the last decade, the invention of piezoresponse force microscopy [13][14][15][16][17] ͑PFM͒ has enabled sub-10 nm resolution imaging of crystallographic and molecular orientations, surface termination, and domain structures in ferroelectric and piezoelectric materials. In materials with switchable polarization, the smallest domain size reported to date is 5 nm and local polarization patterning down to 8 nm has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…At the surfaces of relaxed GaN and AlN crystals, a gradient in the spontaneous polarization induces polarization bound surface charges with densities of 2.12ϫ10 13 and 5.62ϫ10 13 cm Ϫ2 , respectively. The sign of the polarization induced charge at each surface is related to the orientation of the polarization and therefore to the polarity of the crystal.…”
mentioning
confidence: 99%